2021
DOI: 10.14311/cej.2021.02.0036
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Rate of Absorption of Water of Basalt, Polypropylene, and Steel Fibers Reinforced Concrete

Abstract: Good durability of concrete is an essential part of the design process, and tests to determine sustainability have been developed for both laboratory and site use. The main feature of durable concrete is low water absorption. Almost all forms of deterioration in reinforced concrete involve deleterious fluid ingress through the concretes pore structure. In wet concrete, the water ingress rate or other liquids is mostly controlled by absorption due to capillary rise. This study examines the effect of basalt, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Mastali and Dalvand 9 studied the impact resistance, and mechanical behavior of fiber reinforced compacting concrete modified with NS and silica fume. The impact resistance is regarded as one of the critical concrete properties for applications in civil engineering Zhang et al 10 Numerous studies revealed that randomly dispersed steel fibers (SFs) could remarkably improve the concrete mechanical properties, toughness, impact resistance, post crack behavior, and fatigue properties 11–16 . For instance, Zhao et al 17 studied the combined effect of steel slag and hooked‐end SFs on the fresh and mechanical properties of self‐compacting concrete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastali and Dalvand 9 studied the impact resistance, and mechanical behavior of fiber reinforced compacting concrete modified with NS and silica fume. The impact resistance is regarded as one of the critical concrete properties for applications in civil engineering Zhang et al 10 Numerous studies revealed that randomly dispersed steel fibers (SFs) could remarkably improve the concrete mechanical properties, toughness, impact resistance, post crack behavior, and fatigue properties 11–16 . For instance, Zhao et al 17 studied the combined effect of steel slag and hooked‐end SFs on the fresh and mechanical properties of self‐compacting concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The impact resistance is regarded as one of the critical concrete properties for applications in civil engineering Zhang et al 10 Numerous studies revealed that randomly dispersed steel fibers (SFs) could remarkably improve the concrete mechanical properties, toughness, impact resistance, post crack behavior, and fatigue properties. [11][12][13][14][15][16] For instance, Zhao et al 17 studied the combined effect of steel slag and hooked-end SFs on the fresh and mechanical properties of self-compacting concrete. Matalkah et al 18 investigate the effect of fiber type and dosage on the mechanical and shrinkage properties of alkali-activated kaolin binder.…”
Section: Introductionmentioning
confidence: 99%